Poststrukturalistyczne inspiracje w badaniu języka poezji współczesnej - Skibski, Krzysztof (Slavia Occidentalis, 2016)
The text is an attempt to look at the problem of the contemporary studies into poetic language through the prism of poststructuralist reflection. The discussion, which originally referred to the theory of literature, concerned the themes also present in the studies of linguists and resulting from a critical analysis of the assumptions of structuralist thought. The perspective adopted in this abstract made it possible to present a research proposal comprising the category of redundancy in literary communication, as well as – in more detail – the category of relationality of verse, syntactical hypotheses or special predication with regard to poetic language. Free verse is apprehended here with reference to the findings of modern scholars of verse, which involves a special way of thinking about syntax in poetry, and also – about the specific aspects of semantics. The attached examples (from a collection of modern Polish poetry) provide the necessary illustration of the linguistic phenomena demonstrated in the text.